Politeness strategies used by speakers of two Malay dialects / Aimi Syazana Hasnudin - Aimi Syazana, Hasnudin (2012)

(untitled)
This study seeks to identify the employment of Brown and Levinson’s Politeness strategies (1978, 1987) on two Malay dialects, which are the Standard Malay and the Kelantanese dialect. The study intends to identify what politeness strategies were employed when the speakers of these two dialects converse. Consequently, the study also looks into which of the politeness strategies were frequented by the participants when conversing. Based on the findings, despite the dialectal differences, which could be potentially face threatening the results showed that the participants did in fact employ more ‘bald on record’ strategies when conversing among one another. The bald on record strategy is typically known as face threatening as there is no attempt to redress the utterance. However, utterances that were made ‘bald on record’ were not harmful to the rapport of the conversation. In fact, the participants reciprocated. Secondly, the participants were also found to employ more ‘positive politeness’ strategies while interacting. This was an indicator that the participants wanted to maintain solidarity. ‘Negative politeness’ is the next politeness strategy used by the participants. The mutual relationship that the participants already have lend to the fact that negative politeness was not as favored as the previous strategies. This strategy required them to redress their FTAs in a manner that is not intrusive and is respectful of personal space. Lastly, the ‘off record’ strategy was also found in the analysis but is used minimally. Off records are supposedly to be FTAs that are the least threatening as they are very graceful and indirect. In conclusion, the study shows that the participants, regardless of the differences in the dialects they speak, are able to converse mutually despite the dependency on bald on record FTAs.